Preparation and characterisation of silver nanoparticle coated on cellulose paper: evaluation of their potential as antibacterial water filter. Issue 17 (21st November 2016) - Praveena, Sarva Mangala; Han, Lim Suk; Than, Leslie Thian Lung; Aris, Ahmad Zaharin
ABSTRACT: This study investigates the ability of cellulose filter paper coated with silver nanoparticles to remove Escherichia coli from drinking water. The cellulose filter paper was coated with silver nanoparticles by a chemical reduction method using two different ratios of sodium borohydride and silver nitrate. In consideration of drinking-water quality standards and non-carcinogenic health risks, the optimum sodium borohydride:silver nitrate ratio for coating the cellulose filter paper was determined by comparing the silver in the effluent after E. coli removal. For both ratios, 100% E. coli removal was realised. In terms of the silver in the effluent, only the first two lowest concentrations for both ratios of sodium borohydride and silver nitrate were compliant with the drinking-water quality standards, demonstrating hazard quotients (HQs) between 0.084 and 0.484. On the basis of the highest level of E. coli removal with the lowest HQ value, the optimum sodium borohydride:silver nitrate ratio for coating the cellulose filter paper as an antibacterial water filter was 2:1 molar ratio (0.002 M:0.001 M). Silver nanoparticle-coated cellulose filter paper was found to be an inexpensive and easy-to-use emergency antibacterial water filter to generate clean drinking water.